Penggunaan Aplikasi Mentimeter dalam Pembelajaran Daring di Masa Pandemi Covid-19 Pada MGMP PPKn Kabupaten Garut - Tetep Tetep; Ade Suherman; Endang Dimyati; Hermansyah Hermansyah; Prima Melati; Arik Darojat (Jurnal Pekemas, 2020)
The Covid-19 pandemic has a global impact on various sectors, including the education, health, economy, social, cultural and political sectors. The world of education also feels the impact. Changing teaching patterns from conventional learning to online learning is a demand for every educator around the world. Of course every educator needs to master the technology of learning methods and designs to support online learning and educators must ensure that teaching and learning activities continue, even though students are at home. The solution, educators are required to design learning media as an innovation by utilizing online media. This service activity aims to provide knowledge and at the same time practice the use of the meter application in online learning during the Covid-19 pandemic at the MGMP PPKn Garut Regency. This activity was attended by several participants from the national scope of lecturers, students, teachers at all levels of education. This workshop is open to the public, which is the locus of service, namely MGMP PPKn Garut Regency. The one-day workshop was held with the material of introducing the use of the stop meter application to support learning during the Covid-19 pandemic. The results of this service are: 1) Participants are given theoretical and practical material about the meter application, 2) Participants are involved in workshop activities and are also given training on how to use the meter application and are guided by the speaker through zoom meeting interactions, 3) At the end of each participant's session depositing assignments given by the speakers at the workshop activities via email and video display of interaction zoom meetings, 4) The results of the google form that are distributed to the majority of participants understand and can practice using the meter application for online learning